Adult survival and reproductive rate are linked to habitat preference in territorial, year‐round resident Song Sparrows Melospiza melodia. (16th December 2017) - Germain, Ryan R.; Schuster, Richard; Tarwater, Corey E.; Hochachka, Wesley M.; Arcese, Peter
Abstract : Individual animal fitness can be strongly influenced by the ability to recognize habitat features which may be beneficial. Many studies focus on the effects of habitat on annual reproductive rate, even though adult survival is typically a greater influence on fitness and population growth in vertebrate species with intermediate to long lifespans. Understanding the effects of preferred habitat on individuals over the annual cycle is therefore necessary to predict its influences on individual fitness. This is particularly true in species that are resident and territorial year‐round in the temperate zone, which may face potential trade‐offs between habitat that maximizes reproduction and that which maximizes non‐breeding season ('over‐winter') survival. We used a 37‐year study of Song Sparrows Melospiza melodia residing territorially year‐round on a small island to examine what habitat features influenced adult over‐winter survival, how site‐specific variation in adult survival vs. annual reproductive rate influenced long‐term habitat preference, and if preferred sites on average conferred higher individual fitness. Habitat features such as area of shrub cover and exposure to intertidal coastline predicted adult over‐winter survival independent of individual age or sex, population size, or winter weather. Long‐term habitat preference (measured as occupation rate) was better predicted by site‐specific annual reproductive rate than by expected over‐winter survival, but preferred sites maximized fitness on average over the entire annual cycle, . Although adult over‐winter survival had a greater influence on population growth ( λ ) than did reproductive rate, the influence of reproductive rate on λ increased in preferred sites because site‐specific variation in reproductive rate was higher than variation in expected over‐winter survival. Because preferred habitats tended to have higher mean site‐specific reproductive and adult survival rates, territorial birds in this population do not appear to experience seasonal trade‐offs in preferred habitat but are predicted to incur substantial fitness costs of settling in less‐preferred sites.